2012
DOI: 10.1016/j.amepre.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Group-Based Comprehensive Risk-Reduction and Abstinence Education Interventions to Prevent or Reduce the Risk of Adolescent Pregnancy, Human Immunodeficiency Virus, and Sexually Transmitted Infections

Abstract: Based on these findings, group-based comprehensive risk reduction was found to be an effective strategy to reduce adolescent pregnancy, HIV, and STIs. No conclusions could be drawn on the effectiveness of group-based abstinence education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(203 citation statements)
references
References 96 publications
6
190
1
6
Order By: Relevance
“…A difference of 1.4% in unprotected sex has been shown to have a meaningful impact on pregnancy rates. 18,122,124,149 The between-group difference in the incidence of unprotected sex of 1.3% (95% CI 0.5% to 2.2%) by 9 months in our feasibility trial demonstrates that such an effect size is plausible and is consistent with effect sizes seen in the literature. 122 The study will take account of clustering.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A difference of 1.4% in unprotected sex has been shown to have a meaningful impact on pregnancy rates. 18,122,124,149 The between-group difference in the incidence of unprotected sex of 1.3% (95% CI 0.5% to 2.2%) by 9 months in our feasibility trial demonstrates that such an effect size is plausible and is consistent with effect sizes seen in the literature. 122 The study will take account of clustering.…”
Section: Discussionsupporting
confidence: 89%
“…16,18,[121][122][123] Studies indicate that, although other behavioural determinants (such as frequency of sexual intercourse and number of sexual partners) are important, avoidance of unprotected sex via consistent use of contraception is central in explaining variation in levels of teenage pregnancy. 22,124 A reduction in UTP rates would be the ideal primary outcome measure.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 Centers for Disease Control meta-analysis of 66 comprehensive sex education programs for youth regardless of ASD diagnosis found that the programs reduced the frequency of unprotected sexual activity, increased the use of protection (either condoms and/or hormonal contraception), reduced pregnancy, and reduced sexually transmitted diseases [33]. Moreover, research indicates that states that include sexuality education (and not simply abstinence education) have the lowest mean rates of infection among the overall population and among adolescents [34].…”
Section: Disease Dysfunction or Infirmitymentioning
confidence: 99%
“…La evidencia ha demostrado de manera consolidada que, cuando las intervenciones educativas enfocadas en el cambio del comportamiento sexual entre adolescentes eran integrales, lograban ser efectivas 21 al lograr el cambio en la actividad sexual (usar condón o anticonceptivos y reducir el número de parejas sexuales), así como en los niveles de ITS o embarazo. Otros estudios encontraron que la ESI es uno de los programas más efectivos para mejor la SSR, 22 reducir embarazos e ITS y disminuir el comportamiento sexual riesgoso.…”
Section: Educación Sexual Integral En Méxicounclassified